Editorial - Barreto, Édgar Arturo Ramírez (Universidad Santo Tomás, Bogotá, Colombia, 2011)
An essay is evidence of research as well asthe overcoming of obstacles and difficulties. This essay is intended to overcome the difficulty in the “writing” process to go from the reading ability to linking verbal concretions, not of intuitions but of argued ideas.